Penerapan Akad Murabahah Pada Pembiayaan KPR Syariah Di Bank Sumut Capem Syariah HM Yamin - Kusnadi, Hafidah Ayu; Atika, Atika (Universitas Labuhanbatu, 2023)
The needs of human life continue to increase along with the times, from time to time, the population of a country will grow very rapidly from year to year, including the State of Indonesia. The increase in population in Indonesia according to the Central Bureau of Statistics (BPS), a government statistical agency conducts thorough research on the structure of Indonesia's population once every decade. Indonesia has a population of 237.6 million people, this number has increased from the previous decade which amounted to 205.1 million people. Talking about home, home is a basic human need. As the main need for humans, the house is in great demand by many people. However, the skyrocketing house prices meant that it was rare for people to be able to buy a house in cash, so buying on installments or renting was the chosen alternative. There are many ways that can be taken by the community in meeting their basic needs in terms of housing. This research includes field research. This research studies intensively about the background, circumstances, and interactions of a social, individual, group, institution, or society. The researcher saw firsthand the phenomenon that occurred at Bank Sumut Sharia Headquarters HM Yamin. This research is descriptive qualitative.